Evaluating usability and acceptance of a socially assistive robot supported cognitive training for depression – results of the randomized controlled pilot study ‘AMIGA’ - Haeussl, Alfred; Zwigl, Ina; Stojec, Lena; Smolak, Irina; Stijic, Marko; Stross, Tatjana; Lenger, Melanie; Fellendorf, Frederike T.; Guggemos, Suher; Schoenthaler, Elena M. D.; Pszeida, Martin; Orgel, Thomas; et al. (Frontiers in Psychiatry, 2026)
The integration of socially assistive robots (SARs) in mental healthcare offers promising opportunities to enhance traditional treatments. The humanoid SAR “Pepper” has shown potential for supporting cognitive and emotional interventions for individuals. While SAR acceptance has been explored in general healthcare, limited evidence exists regarding its usability and acceptance among individuals with affective disorders. This study aimed to assess the usability and acceptance of “Pepper” as an adjunct motivational technology in combination with tablet-based cognitive training, compared to tablet training alone, among inpatients with depression, focusing on sex-specific differences. A randomized controlled trial was conducted between June and October 2024 with 32 inpatients diagnosed with depression. Participants were randomly assigned to one of two groups: the SAR group, which used “Pepper” together with the cognitive training app “Multimodal Activation” in combination with motivational feedback, and the control group, which used the same app on a tablet without motivational feedback. Each participant completed two cognitive training sessions of approximately 10 to 20 minutes. Standardised questionnaires, namely, Technology Acceptance Model (TAM), System Usability Scale (SUS), and Technology Usage Inventory (TUI), were administered after the second session. To analyze group and sex differences, analyses of co-variance were used for single-scale measures (SUS, TUI Overall), and multiple analyses of co-variances were used for instruments with multiple subscales (TAM, TUI). A significant group difference was found in the SUS score, favoring the SAR group. The SAR group also scored higher in the TUI User-Friendliness, while the tablet group showed higher scores in Accessibility. Regarding sex differences, female participants scored higher on the TUI Overall and Scepticism subscales than male participants. These findings suggest that SAR-supported cognitive training is a viable and accepted tool for supporting cognitive training in psychiatric care. High usability and positive acceptance ratings indicate its potential to complement conventional therapies. The observed sex-specific differences underline the relevance of tailored robotic interventions. Limitations of this study include the small sample size and short intervention period. Further studies are warranted to validate these findings and examine the ethical considerations and human–robot interaction dynamics in psychiatric settings.